Segmented filamentous bacteria-induced epithelial MHCII regulates cognate CD4+ IELs and epithelial turnover - Brabec, Tomáš; Schwarzer, Martin; Kováčová, Katarína; Dobešová, Martina; Schierová, Dagmar; Březina, Jiří; Pacáková, Iva; Šrůtková, Dagmar; Ben-Nun, Osher; Goldfarb, Yael; Šplíchalová, Iva; Kolář, Michal; et al. (The Journal of experimental medicine, 2024)
Intestinal epithelial cells have the capacity to upregulate MHCII molecules in response to certain epithelial-adhesive microbes, such as segmented filamentous bacteria (SFB). However, the mechanism regulating MHCII expression as well as the impact of epithelial MHCII-mediated antigen presentation on T cell responses targeting those microbes remains elusive. Here, we identify the cellular network that regulates MHCII expression on the intestinal epithelium in response to SFB. Since MHCII on the intestinal epithelium is dispensable for SFB-induced Th17 response, we explored other CD4+ T cell-based responses induced by SFB. We found that SFB drive the conversion of cognate CD4+ T cells to granzyme+ CD8α+ intraepithelial lymphocytes. These cells accumulate in small intestinal intraepithelial space in response to SFB. Yet, their accumulation is abrogated by the ablation of MHCII on the intestinal epithelium. Finally, we show that this mechanism is indispensable for the SFB-driven increase in the turnover of epithelial cells in the ileum. This study identifies a previously uncharacterized immune response to SFB, which is dependent on the epithelial MHCII function.
Keywords: prezentace antigenu; granzymy; CD4-Positive T-Lymphocytes; Granzymes; Epithelial Cells; Antigen Presentation; Bacteria; epitelové buňky; CD4-pozitivní T-lymfocyty